The business of pilgrimage in the fifteenth-century Venice - Di Stefano, Laura G. (2019)
In the last two centuries, scholars provided a great deal of attention to travel literature and its dissemination, especially regarding the subject of pilgrimage and its understanding as a spiritual and emotional experience. Nevertheless, pilgrimage has been barely considered in terms of “business” in particular concerning the involvement of Venice in the organization of galleys departures towards Jerusalem. Indeed, only a few studies offer a deep comprehension of the pilgrimage journeys under a socio-economic perspective, which may have shaped the production and dissemination of its related travel literature. The scope of this thesis called ‘The business of pilgrimage in the fifteenth-century Venice’ is to assess the importance of Venice from an economic and religious perspective in relation to the organization of pilgrimage departures during the fifteenth century. The core of dissertation is divided in two main parts. The first part, explores the evolution of Venice from main port of departure towards Jerusalem to religious point of interest within the Holy Land pilgrimage. In particular, chapter three, Pilgrims in the hands of Venetians, offers significant investigation about the management of pilgrimage departures and pilgrims arrivals in Venice since the thirteenth century. This examination is carried out through the analysis of the oldest Venetian legislation related to the field of pilgrimage and the study of the personal involvement of certain Venetian noble families (e.g. the Contarini and the Morosini) in the administration of galleys departures and promotion of religious itineraries in the city. Venetian religious development as a “city for pilgrims” is fully explored in chapter four, Venice as an altera Hierusalem? This chapter investigates the way in which Venice gradually turned into a counterpart of Jerusalem within the itinerarium ad loca sancta by replicating the Holy Land’s system of religious and spiritual experience in its social structures (e.g. through the creation of receptive structures for pilgrims or through the creation of indulgences tour along the Venetian churches). The second part of the thesis surveys how pilgrims perceived Venice in their travel writings and whether these have been influenced by Italian culture. In this perspective chapter five, William Wey and the matter of Venice, analyses, in form of case study, the two pilgrimages to Jerusalem made by the English pilgrim in 1458 and 1462, evaluating the pilgrim’s perception of Venice both from an economic and religious point of view. A broader investigation about Venice dual role in late medieval travel literature has been done in chapter six, Venice and the fifteenth-century travellers. This chapter assesses whether descriptions of Venice in western European pilgrimage literature produced by the fourteenth and fifteenth centuries may have been affected by external factors such as pilgrims’ nationalities or the Venetian behaviour upon their arrival. Chapter seven, presents a second case study, which includes the analysis of an unpublished travel logbook testifying a journey from Venice to Jerusalem in 1409. This logbook, officially Venezia, Archivio di Stato, Diario di navigazione, Miscellanea, Atti, Diversi Manoscritti, Busta 134, Doc. 14, has been discovered to be the only surviving evidence of Venice smuggling of cotton through pilgrimage galleys. This gives a clear demonstration about the extent of the complex economics and religious links developed by Venice with different people and institutions during the monopoly of pilgrimage departures in the fifteenth century. This research redefines the way in which pilgrimage religious experience has been scholarly understood until know and aims to open new academic discussion about Venice’s leading role in pilgrimage during the late medieval period.